DSCR1 is required for both axonal growth cone extension and steering - Wang, Wei (J Cell Biol, 2016)
Local information processing in the growth cone is essential for correct wiring of the nervous system. As an axon navigates through the developing nervous system, the growth cone responds to extrinsic guidance cues by coordinating axon outgrowth with growth cone steering. It has become increasingly clear that axon extension requires proper actin polymerization dynamics, whereas growth cone steering involves local protein synthesis. However, molecular components integrating these two processes have not been identified. Here, we show that Down syndrome critical region 1 protein (DSCR1) controls axon outgrowth by modulating growth cone actin dynamics through regulation of cofilin activity (phospho/dephospho-cofilin). Additionally, DSCR1 mediates brain-derived neurotrophic factor–induced local protein synthesis and growth cone turning. Our study identifies DSCR1 as a key protein that couples axon growth and pathfinding by dually regulating actin dynamics and local protein synthesis.